1987
DOI: 10.1128/aac.31.2.238
|View full text |Cite
|
Sign up to set email alerts
|

BMY 28100, a new oral cephalosporin

Abstract: BMY 28100, a new oral cephalosporin with a (Z)-propenyl side chain at the 3 position and a phydroxyphenylglycyl substituent at the 7 position, was evaluated in comparison with cefaclor and cephalexin and, when appropriate, ampicillin and vancomycin. In vitro, BMY 28100 was more active than the reference cephalosporins against streptococci, Staphylococcus aureus, Staphylococcus epidermidis, Listeria nionocytogenes, Haemophilus influenzae, Propionibacterium acnes, Clostridiunm perfrigens, and Clostridium diffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
30
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 11 publications
(5 reference statements)
3
30
0
Order By: Relevance
“…The antimicrobial spectrum of BMY-28100 is superior to those of cephalexin and cefadroxil and similar to that of cefaclor (1,3). Animal studies suggest that BMY-28100 may have some pharmacokinetic advantage over cefaclor (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The antimicrobial spectrum of BMY-28100 is superior to those of cephalexin and cefadroxil and similar to that of cefaclor (1,3). Animal studies suggest that BMY-28100 may have some pharmacokinetic advantage over cefaclor (6).…”
mentioning
confidence: 99%
“…It has a phydroxyphenylglycyl substituent at position 7 and a propenyl side chain at position 3. Its antimicrobial spectrum includes important gram-positive and gram-negative organisms usually associated with infections of the urinary and respiratory tracts (1,3,6,11). The antimicrobial spectrum of BMY-28100 is superior to those of cephalexin and cefadroxil and similar to that of cefaclor (1,3).…”
mentioning
confidence: 99%
“…Cefprozil consists of the cis and trans isomers in a ratio of 9:1. It has a spectrum of activity similar to that of cefaclor but greater activity against staphylococci and Haemophilus influenzae (1,2,10,12). It is also active against group A streptococci (2) and Branhamella catarrhalis (1).…”
mentioning
confidence: 91%
“…Only trace amounts of trans isomer were found in the tonsillar and adenoidal tissue. The estimated time for cefprozil concentrations in the tonsil tissue to remain above the MIC for S. pyogenes, which commonly causes tonsillitis (1,2,10,12), is more than 9 h. In the clinical efficacy trial of treatment of pharyngitis or tonsillitis, clinically significant improvement (86% eradication) was observed (11). This study demonstrated that the excellent penetration of cefprozil into tonsillar and adenoidal tissue corresponds well with the clinical outcome.…”
mentioning
confidence: 99%
See 1 more Smart Citation